Molecular identification and function characterization of four finTRIM genes from the immortal fish cell line, EPC. (December 2020) - Li, Yi-Lin; Zhao, Xiang; Gong, Xiu-Ying; Dan, Cheng; Gui, Jian-Fang; Zhang, Yi-Bing
Abstract: In mammals, tripartite motif (TRIM)-containing proteins are involved in interferon (IFN)-mediated antiviral response as pivotal players endowed with antiviral effects and modulatory capacity. Teleost fish have a unique subfamily of TRIM, called finTRIM (fish novel TRIM, FTR) generated by genus- or species-specific duplication of TRIM genes. Herein, four TRIM genes are identified from Epithelioma papulosum cyprini (EPC) cells, and phylogenetically close to the members of finTRIM, thus named FTREPC1, FTREPC2, FTREPC3 and FTREPC4. Despite high similarity in nucleotide sequence, FTREPC1/2 genes encode two proteins with a typically consecutive tripartite motif followed by a C-terminal B30.2 domain, while FTREPC3/4-encoding proteins retain only a RING domain due to early termination of translation. They are induced by poly(I:C), GCRV and SVCV as IFN-stimulated genes (ISGs), and this induction is severely impaired by blockade of STAT1 pathway and is dependent on a typical ISRE motif within the 5′ untranslated regions (5′UTRs) of FTREPC1/2/3/4 genes. Whereas overexpression of FTREPC1/2/3/4 alone does not activate fish IFN promoters, overexpression of FTREPC1 or FTREPC2, rather than FTREPC3 and FTREPC4, significantly impairs intracellular poly(I:C)-triggered activation of fish IFN promoters. Consistently, FTREPC1/2 promote virus replication through negatively regulating IFN response. Our results provide evidence for the involvement of EPC finTRIM proteins in IFN antiviral response and insights into genus- or species-specific regulation of fish innate immune pathways. Highlights: FTREPC1/2/3/4 are four finTRIM genes of EPC origin. FTREPC1/2/3/4 are four typical ISGs with an ISRE motif within their 5′UTRs. FTREPC1/2 promote virus replication through negatively regulating fish IFN response.